A Simple, Low-cost, Efficient and Smart Consumer Gas Leakage Detection System - Kommey, Benjamin; Opoku, Daniel; Lartey, Jessica; Kumah, Kirston; Tantuo, Mark (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2022)
Liquefied Petroleum Gas is used for a wide range of both domestic and industrial purposes. Its use has seen a significant increase over the years. Unfortunately, there have also been many casualties resulting from gas explosions in recent times. Often, there is a news report of a gas explosion occurring somewhere, whether at home, in the marketplace or in an industry. Although these accidental explosions are sometimes beyond human control, some are due to ignorance, negligence, or improper care of gas cylinders. Most explosions are caused by undetected gas leakages which are then set off to explode with the slightest ignition. Apart from explosions, fires at homes can also be caused by gas leakages. This usually results in serious injuries, loss of property and even sometimes, loss of lives. This project seeks to provide a smart, budget friendly and easy to use gas leakage detector system, a better alternative to relying on the natural way of using the nose, which may fail and in effect, incur undesirable consequences. The system employs an MQ2 sensor interfaced with an ESP8266 Wi-Fi module for sensing the gas in the atmosphere and displaying an alert message on the lcd. The Wi-Fi in combination with the microcontroller module acts as the transmission and processing unit, allowing for communication over wireless medium. This way, a user can receive notifications on a mobile device depending on changes the hardware system detects in the atmosphere. There is also a buzzer to alert nearby persons by sound so that they can take the necessary precautions and actions